Effect of wick application of growick irrigation system on the cultivation of pakcoy in sand tailing media from post-tin mining land - Ismed Inonu; Roby Hambali; Deni Pratama; Ayu Wirda Lestari (Brawijaya University, 2021)
A large part of post-tin mining land covered by sand tailing which has low water storage capacity, making it vulnerable to drought stress. The innovation of irrigation technology has been developed to overcome this problem such as capillary irrigation system combined with groasis system using a large reservoir with hydroponic wick system called the growick system. This study aimed to determine the best number and type of wick in growick irrigation system to water consumption and also growth and yield of pakcoy cultivated in sand tailing media. The research was conducted from February to June 2020 at Experimental field of Universitas Bangka Belitung, Indonesia. Treatments consisted of the types of wick (flannel and stove wick) and numbers of wick per polybag (1, 2, 3, and 4 wicks). The study used a completely randomized factorial design with 3 replications. Data obtained were analyzed using Analysis of Variance continued with Duncan's Multiple Range Test (DMRT) at 95% significant level. The result showed that usage of flannel wick gave the highest results of growth and yield of pakcoy but it absorbed more water than stove wick. Flannel wick also had lower water usage efficiency than stove wick. The use of single wick gave the highest result of growth and yield of pakcoy than using more wicks. Results of the study showed that single wick treatment gave the highest growth and yield of pakcoy. Flannel wick gave the highest growth and yield of pakcoy, but it was not significantly different from stove wick. Single flannel wick treatment showed no significant difference with single stove wick treatment in growth and yield of pakcoy except for water usage volume parameter. Flannel wick absorbed more water than stove wick, so it has lower water usage efficiency than stove wick. Application growick system using 1 stove wick was the best treatment for cultivating pakcoy in sand tailing media from post-tin mining land.